Not really an aftermath. The role of actual construction in the design process of the Sydney Opera House roof - Paolo Stracchi; Luciano Cardellicchio; Paolo Tombesi (Frontiers of Architectural Research, 2023)
For the past 50 years, the Sydney Opera House has been the subject of a prodigious hagiography of the personalities involved in its realization and their legendary querelles. Yet it remains paradoxically unexplored when it comes to its operative construction decisions, particularly those that relate to the erection of its renowned superstructure. Through the analysis of a newly discovered set of shop drawings prepared for the innovative formwork system of the iconic roof sails, the paper contributes to the construction history of the building whilst shedding light on the hitherto unacknowledged role of the general contractor in the design process. In doing so, it questions the validity of conventional assumptions about the technical division of labour in complex projects, where construction and project management tend to be kept separate from architectural and structural design, furthermore suggesting the need for broader design exegeses, combining project-based and production-based concerns. In reflecting on its import for contemporary practice, the study suggests that the revealing picture of the Sydney Opera House project, as it emerged from the cumbersome archive-based cross-analysis of the manual documentation produced for it, is in principle much easier and perhaps important to obtain today. This is due, on the one side, to availability and diffusion of digital project collaborative platforms; on the other side, to the merging and the blurring of professional and non-professional design contributions.